Historical Semantics of the Class Concept in Academic Literature: The Experience of Quantitative Analysis - Sergei Korotaev (Journal of Economic Sociology, 2024)
The paper is devoted to the quantitative analysis of semantic changes in the meaning of a concept of “class” in the sociological texts from the second third of the twentieth century to the present. The relevance of the study is conditioned by the lack of clarity and multiple meanings of the concept in question. This ambiguity has led to numerous fruitless discussions about definitions, exemplified by the famous debate on the “death of class”. In contrast to existing works on the history of “class” concept based on close engagement with a limited number of specialized sources, the focus of this paper is to explicate the term's common usage across a wide range of topics in sociological publications. The analysis is based on a corpus of abstracts from the leading sociological journals using quantitative methods. A key question is to what extent the well-known discussions of experts on class analysis have influenced the widespread use of the concept by sociologists. A number of additional questions aimed at identifying the factors determining the dynamics of the term's use were also considered: to what extent the word “class” has retained the conflict connotations derived from Marxism; and whether there is a connection between this concept and terminology denoting statistical methods. Proceeding from the fact that the concept can be expressed by different words in different periods of time in different texts, we examined the semantic field which included, in addition to “class”, a number of related terms such as “stratification” and “mobility”. According to the analysis, most of the examined terms have remained relatively stable in their semantics. Nevertheless, a few changes of the class definition, known from the core literature, have affected its practical usage. However, as one can assume, the general “disciplining” effect of numerous publications by major authors is fading, which allows us to formulate the hypothesis that “class” is losing its conceptual content, turning into a metaphor, and its use in sociological texts is getting closer to non-academic.